Рак прищитоподібної залози: клініко-морфологічні особливості - Огризько, Т. В.; Гузь, О. О.; Шептуха, С. А.; Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2014)
Parathyroid carcinoma (PC) is the most rare human cancer and cause of primary hyperparathyroidism. Preoperative diagnosis of this disease is always a difficulty. We report a case of PC with hypercalcemia. Intrathyroid tumor localization was the cause of diagnostic error in the preoperative period. On the basis of elevated levels of serum PTH and the results of scintigraphy was operated. Final pathological report confirmed the diagnosis of PC. Thus, the high frequency of diagnostic errors in the differential diagnosis of parathyroid disease and multinodular goiter requires a comprehensive clinical and laboratory diagnostic approach.